Condensation and thermalization of an easy-plane ferromagnet in a spinor Bose gas - Prüfer, Maximilian; Spitz, Daniel; Lannig, Stefan; Strobel, Helmut; Berges, Jürgen; Oberthaler, Markus K. (Arxiv, 2022)
The extensive control of spin makes spintronics a promising candidate for future scalable quantum devices. For the generation of spin-superfluid systems, a detailed understanding of the build-up of coherence and relaxation is necessary. However, to determine the relevant parameters for robust coherence properties and faithfully witnessing thermalization, the direct access to space- and time-resolved spin observables is needed. Here, we study the thermalization of an easy-plane ferromagnet employing a homogeneous one-dimensional spinor Bose gas. Building on the pristine control of preparation and readout we demonstrate the dynamic emergence of long-range coherence for the spin field and verify spin-superfluidity by experimentally testing Landau's criterion. We reveal the structure of the emergent quasi-particles: one 'massive'(Higgs) mode, and two 'massless' (Goldstone) modes - a consequence of explicit and spontaneous symmetry breaking, respectively. Our experiments allow for the first time to observe the thermalization of an easy-plane ferromagnetic Bose gas; we find agreement for the relevant momentum-resolved observables with a thermal prediction obtained from an underlying microscopic model within the Bogoliubov approximation. Our methods and results pave the way towards a quantitative understanding of condensation dynamics in large magnetic spin systems and the study of the role of entanglement and topological excitations for its thermalization.
Gesehen am 20.09.2022